Prawo bez autorytetu – prawo pozbawione sumienia... - Bałandynowicz, Andrzej (Horyzonty Wychowania, 2017)
Andrzej Bałandynowicz’s text takes up the central topic of conscience in the context of the existing condition of law in Poland. Law „without conscience” is, according to the author’s analyses, the effect of a gap the system of formal regulations and the universal system of moral beliefs shared by the society. The fundamental demand here is then the return to law finding its roots in morality. In this way it will regain authority, indispensable also as far as its actual effectiveness is concerned. The author’s reflection is focused on specific, binding legal solutions within the scope of social service activity and criminal responsibility system functioning. In both cases, the deficiencies – contrary to the functions declared – result in the deepening of segregation and social exclusion of individuals processes.